Economic Capacity and Development Strategies for Arfak Tribe Farmers in Manokwari, West Papua - Tapi, Triman; Mikhael; Yohanis Yan Makabori; Asep Mulyana (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
This study was carried out to examine the economic well-being and capacity of Arfak Tribe farmers in Manokwari, West Papua. It focused on investigating the factors influencing economic capacity in the context of the 2011–2016 Manokwari Medium-Term Regional Development Plan (RPJMD), which aimed at poverty reduction. Furthermore, the descriptive analysis, differential tests, and regression analysis were used to compare the economic conditions between Arfak Tribe and non-Papuan farmers. The results showed significant disparities, where non-Papuan farmers enjoyed higher income, skills, capabilities, greater access to agricultural technology, adequate capital and work ethic compared to Arfak Tribe. Cultural factors and social capital had a significant negative impact on the income and savings levels. These results emphasized the importance of targeted assistance to strengthen the knowledge and skills of Arfak farmers. The effective use of financial assistance from the central and regional governments supported the economic development of this indigenous local community. Targeted assistance and financial support improved the situation for Arfak farmers, addressed the systemic issues such as unequal access to resources and opportunities that perpetuated poverty. In conclusion, this study provided valuable insights on policy interventions used to improve well-being and economic empowerment of indigenous local farmers.